Dietary Habits of Insectivorous Bats (Family Hipposideridae) in The Rice Field - Nur Sakinah Humairah Zanarudin; Nurul Ain Elias; Suhaila Ab Hamid (Tropical Life Sciences Research, 2025)
This study establishes a foundational understanding of the dietary preferences of two insectivorous bats (Family Hipposideridae), Hipposideros larvatus and Hipposideros cineraceus caught in the rice field areas. The investigation focused on the analysis of their fecal pellets collected in areas near Gunung Keriang, Kota Setar, Kedah. A total of 40 pellets from eight individuals were meticulously examined. These eight bats were categorised into two distinct groups based on sex and reproductive stages (lactating and non-reproductive) from the two bat species. The dietary composition of H. larvatus comprised 55.2% Coleoptera, 23.2% Lepidoptera, 10.1% Hemiptera, 9.2% Diptera and 2.1% Hymenoptera. The diet of the bat species was significantly dominated by Coleoptera, accounting for over half of the overall dietary percentage. On the contrary, H. cineraceus, exhibited a different diet composition, with 68.0% Lepidoptera, 18.5% Coleoptera, 7.0% Diptera, 5.1% Hemiptera and 0.6% Hymenoptera. These variations in dietary preferences can be attributed to factors such as their differing abilities to digest chitin found on the elytra (forewing) of beetles, variations in size between the two species, distinct echolocation frequencies, and differing reproductive states. Both H. larvatus and H. cineraceus have the potential to serve as effective pest controllers in rice fields by reducing insect pest populations, especially from the order Lepidoptera (rice stem borer) and Hemiptera (leafhoppers). Further research should be conducted in different locations to gain a more comprehensive understanding of these bat species' diets and whether they exhibit exclusive or generalised feeding patterns.